2010
DOI: 10.1002/crat.201000125
|View full text |Cite
|
Sign up to set email alerts
|

Formation and ageing of L‐glutamic acid spherulites

Abstract: Polycrystalline spherulites of L-glutamic acid have been crystallized by pH-shift precipitation from stirred aqueous solutions. The time dependent behaviour of the spherulites has been studied during the crystallization process and batch filtration tests have been performed. It has been shown that the FBRM mean chord length of the investigated spherulites decreases in the course of time. The fact that the size reduction progresses faster at higher temperature and the solubility of resuspended polycrystalline p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 16 publications
(19 reference statements)
1
10
0
1
Order By: Relevance
“…Spherulitic growth is observed most frequently in crystals formed ion-byion from solution 43 , in sulphates 49,50 and oxalates 51 , or via phasetransformation, for instance in the case of glass to crystalline phase, e.g. in small organic molecules 52,53 , or crystallization of polymers from the melt, e.g. in plastics 54 or metals 54,55 .…”
Section: Discussionmentioning
confidence: 99%
“…Spherulitic growth is observed most frequently in crystals formed ion-byion from solution 43 , in sulphates 49,50 and oxalates 51 , or via phasetransformation, for instance in the case of glass to crystalline phase, e.g. in small organic molecules 52,53 , or crystallization of polymers from the melt, e.g. in plastics 54 or metals 54,55 .…”
Section: Discussionmentioning
confidence: 99%
“…17 Rodrigues-Navarro also showed this effect. 18 Thus, both aragonite growth by CPA and by ion attachment are faster along the c-axis.Spherulites are found in a wide variety of materials systems, including geologic minerals, 19,20 metal alloys, 21 nonmetallic elements, 5,22 salts, 23,24 organic molecules, 13,25 proteins, 26 and a vast number of synthetic 2,3,27,28 and natural 4 polymers.Many biominerals have also been described as spherulitic based on their morphologies, including coral skeletons, 10,11,29,30 avian eggshells, 31−33 fish otoliths, 12,34,35 crustacean statoliths, 36 sponges, 37 and kidney stones. 38,39 The only evidence of spherulites in biominerals obtained from crystal orientation analysis, however, is in bioinduced, kidney stones, which are calcium oxalate monohydrate pathological biominerals.…”
mentioning
confidence: 99%
“…5). The observation of the flakes is reminiscent of the behaviour of L-glutamic acid crystals [10] after 3 h of crystallization and could indicate a modification of crystal-solution interaction during the crystallization process. The cake resistance of 1,8·10 11 m/kg is higher than for experiments in which the stirring speed was kept constant at 500 rpm (6,1·10 10 m/kg) which can also be accounted for by the lower measured mean chord length of 12.4 µm as compared to 16.1 µm (unweighted).…”
Section: Resultsmentioning
confidence: 90%
“…Louhi-Kultanen et al [15], for example studied the ageing of crystalline potassium sulphate and found that 60 min ageing time decreased the cake resistances whereas cake porosities varied only slightly between fresh and aged precipitates. As a further example, Beck et al [10] have shown that the average specific cake resistance of L-glutamic decreases when kept in a stirred aqueous solution for 22 h. Like for the aromatic amine, differences in the XRD spectra of crystals from different time intervals have been shown to be marginal, if they exist at all.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation